PENGARUH PERSEPSI KEADILAN PAJAK WAJIB PAJAK ORANG PRIBADI TERHADAP PERILAKU KEPATUHAN FORMAL - Aisyah Nur Heniar; Mienati Somya Lasmana (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2013)
This study aims first to examine whether there is the influence of perceived tax fairness on individual taxpayers compliance behaviour. The second bjective is to examine whether there is a moderating role of financial condition in the relation of perceived tax fairness on individual taxpayers compliance behaviour. The study was conducted in KPP Pratama Sidoarjo Utara by questionnaire survey method to 100 individual taxpayers. Moderated Regression Analysis was used to identify the study variables (perceived tax fairness, financial condition, and tax compliance). The results of this study indicate that there is a statistically ignificant influence of perceived tax fairness to the level of tax compliance behavior. The subvariabels of tax fairness identified are general tax fairness, tax rate structure, self interest, and special provisions, but the taxpayers consider the exchange with government is not fair enough. The financial condition also has a significant moderating influence of perceived tax fairness to the level of tax compliance behaviour.